(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Effects of gender and place of residence on personality characteristics of children were studied. A total of 400 children were the sample of this study of which 200 were from urban and 200 from rural area. Results revealed that male children were more aggressive than female. There was no difference between urban and rural children in aggressiveness vs submissive‐ness. The effects of gender and residence on extroversion vs introversion were not significant. The male children were more relaxed than female children. The effect of residential status on relaxed vs tense was not significant. Dhaka Univ. J. Biol. Sci. 24(1): 59-64, 2015 (January)